If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + 24 = 11m Reorder the terms: 24 + 9m = 11m Solving 24 + 9m = 11m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-11m' to each side of the equation. 24 + 9m + -11m = 11m + -11m Combine like terms: 9m + -11m = -2m 24 + -2m = 11m + -11m Combine like terms: 11m + -11m = 0 24 + -2m = 0 Add '-24' to each side of the equation. 24 + -24 + -2m = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -2m = 0 + -24 -2m = 0 + -24 Combine like terms: 0 + -24 = -24 -2m = -24 Divide each side by '-2'. m = 12 Simplifying m = 12
| 17n=5n+72 | | 2x+44=7 | | 2[5x+3]-2=14 | | [2x+5]=3x+4 | | [2x+5]=3x | | [2x]=-4 | | 8x+11+10x+82+105=360 | | [-8x]=32 | | [x-6]=15 | | x(x-1)=-x+1 | | 2x^2-23x+63=0 | | 6x^2-1x-1=0 | | 3x^2-26x+35=0 | | 2x^2+21x+54=0 | | 7x-(5x+3)=5(x-3)+2 | | x*3+8=8*x-64*x | | x*3+8=8x-64*x | | a*6=20 | | 7x^2-1=0 | | 80=100-5x | | a+(a-3)=(a+4)-(a-1) | | a+(a-3)=(a+4)-(a-1)(a+2) | | 4m-4=6m | | Y-12=12x | | 2y-6x=8 | | 15x^3-9x-6x= | | 15x-9x-6x= | | 25s^2+5s-42= | | 8x-2=-9-7x | | 6-q=12 | | 100x^2+121=0 | | x^2+36+3= |